Improved battery production process

By using a combination of high-purity zinc and collaborative electrode materials in the dry battery, the problems of bottom cover deformation and insufficient safety are solved, and the high safety performance and long life of the battery are achieved.

CN119674113AInactive Publication Date: 2025-03-21HANGZHOU CHANGMING BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510199999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing dry battery production technology, the thermal expansion coefficient of the bottom cover material is not fully considered, which leads to deformation of the bottom cover, affects the sealing and contact performance of the battery, and increases the risk of liquid leakage and explosion.

Method used

The cylinder shell is made of high-purity zinc as the negative electrode, and the positive electrode material is prepared using materials such as manganese dioxide, silicon oxide, graphite powder and glucose. Through the coordinated electrode structure and unique battery assembly process, the mechanical strength and safety performance of the battery are improved.

Benefits of technology

It significantly improves the safety performance and reliability of the battery, extends the battery life, and reduces the risk of fluid leakage and explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674113A_ABST
    Figure CN119674113A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to an improved battery production process. The process comprises the following steps: 1) manufacturing a cylindrical shell by taking high-purity zinc as a raw material, wherein the cylindrical shell is a negative electrode; 2) preparing a positive electrode material by taking manganese dioxide, silicon dioxide, graphite powder and glucose as raw materials, and grinding the positive electrode material into positive electrode powder; and 3) filling, assembling and sealing the cylindrical shell and the positive electrode powder to prepare the improved battery. Through the synergistic effect of the component materials in the battery, the ion transmission rate, the mechanical strength and the enhanced safety performance in the battery are improved; through a unique battery assembly process, the special electrode material cavity distribution is optimized, the stress concentration in the battery is reduced, and the electron transmission efficiency is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to an improved battery production process. Background Art

[0002] In the manufacturing process of dry batteries, due to the influence of various factors such as production technology and raw materials, the bottom cover problems of non-compliant products often occur. These problems may cause poor battery contact, leakage, and even serious consequences such as battery explosion. In order to deal with these problems, the industry has carried out a series of studies. At present, although the mainstream dry battery production technology on the market has reduced the incidence of bottom cover problems to a certain extent, there are still some shortcomings. For example, some production technologies fail to fully consider the thermal expansion coefficient of the material when manufacturing the bottom cover, which causes the bottom cover to be easily deformed during use, thereby affecting the sealing and contact performance of the battery. In addition, some production technologies also have defects in the connection method between the bottom cover and the battery body, such as unstable connection and easy loosening, which increase the risk of battery leakage and explosion. Therefore, it is particularly urgent to improve the efficiency of dry battery bottom cover defect detection, and it is urgent to find an effective solution. Summary of the invention

[0003] The technical solution of the present invention aims at the defects of batteries in the prior art solutions such as leakage and explosion, and provides an improved battery production process.

[0004] The main purposes of the present invention are: 1. Improving the safety performance of the battery.

[0005] 2. Improve battery reliability.

[0006] 3. Extend battery life.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions.

[0008] An improved battery production process, the process comprising: 1) using high-purity zinc as a raw material to manufacture a cylindrical shell, the cylindrical shell being a negative electrode.

[0009] 2) Prepare positive electrode materials using manganese dioxide, silicon dioxide, graphite powder and glucose as raw materials, and grind them into positive electrode powder.

[0010] 3) The cylindrical shell and the positive electrode powder are filled, assembled and sealed to prepare an improved battery.

[0011] Preferably, the high-purity zinc in step 1) is metallic zinc with a purity of ≥ 97.0 wt%; and the manufacturing of the cylindrical shell in step 1) is achieved by a stamping process.

[0012] Preferably, in step 2), the mass ratio of manganese dioxide, silicon dioxide, graphite powder and glucose is 0.1:(0.2-0.3):4:(0.8-1.2).

[0013] Preferably, the process of preparing the positive electrode material in step 2) is: mixing manganese dioxide, silicon dioxide, graphite powder and glucose in proportion, reacting at a temperature of 240-260°C for 12-16 hours, and then drying at a temperature of 130-150°C for 6-8 hours.

[0014] Preferably, the mesh size of the positive electrode powder in step 2) is 50-150 meshes.

[0015] Preferably, the filling, assembling and sealing process of step 3) is as follows: placing the pulp layer paper into the zinc cylinder, then placing the bottom paper into the zinc cylinder, placing the positive electrode powder battery cell in the zinc cylinder, performing a negative pressure treatment with a re-pressure ring inside the zinc cylinder, inserting a carbon rod, closing the zinc cylinder, using sealing glue, adding an outer seal and an integrated cover, and then loading and storing.

[0016] Preferably, the products loaded and stored on the tray are subjected to bottom brushing and electrical testing, and the iron bottom is heat-shrunk, loaded into the iron shell, and the locking procedure is performed, and finally the heat-shrunk is performed.

[0017] The process flow of the technical solution of the present invention is as follows Figure 1 As shown, the core lies in the use of manganese dioxide, silicon dioxide, graphite and glucose to construct an electrode structure with a synergistic effect, thereby improving the mechanical strength of the internal structure of the battery while ensuring the passage of ions.

[0018] In the existing technical solutions, most of the negative electrode materials of batteries are made of carbon materials, among which graphite is relatively cheap and has a large production scale, and is widely used in the commercial preparation of negative electrode materials for batteries. However, the theoretical specific capacity of graphite is low, which greatly limits the capacity and service life of the battery. In addition, graphite is prone to volume expansion and contraction during discharge, resulting in damage to the internal structure of the battery, affecting the discharge stability and safety of the battery.

[0019] In the technical solution of the present invention, manganese dioxide can provide numerous redox active sites in the battery electrode due to its rich oxidation states and unique crystal structure, participate in electrochemical reactions, and play a vital role in the energy storage and release of the battery. However, a single manganese dioxide electrode usually faces the problem of insufficient mechanical stability, and is prone to structural collapse during the charge and discharge process, thereby affecting the cycle life of the battery. Silicon dioxide is known for its excellent chemical stability and outstanding mechanical properties. It can serve as a physical support skeleton to enhance the mechanical strength of the electrode. In addition, the porous structure of silicon dioxide provides channels for ion transport, which helps to improve the ion conductivity of the battery. Graphite, as a traditional electrode material, exhibits excellent electronic conductivity. Its layered structure can accommodate the embedding and de-embedding of lithium ions, and realizes efficient charge storage and transfer during the battery charge and discharge process. The presence of graphite significantly improves the electronic conductivity of the electrode, ensures the rapid transmission of electrons inside the battery, and reduces the internal resistance of the battery. In this system, glucose plays a special role. Through treatment methods such as high-temperature carbonization, glucose can be converted into a carbon material with a rich pore structure. These carbon materials not only further enhance the conductivity of the electrode, but also can be interwoven with other materials to form a three-dimensional network structure, promoting the synergistic effect between the components.

[0020] The synergistic electrode structure shows excellent performance in ensuring ion transmission. The porous silica structure is combined with the rich pores formed by the carbon material to provide an unobstructed transmission path for ions. Ions can diffuse rapidly in these pores, ensuring the high efficiency of ion transmission during the charge and discharge process of the battery and maintaining the excellent electrochemical performance of the battery. The synergistic effect plays a significant role in enhancing the mechanical strength of the internal structure of the battery. As a rigid skeleton, silica provides basic support for the electrode structure. The layered structure of graphite is stacked on each other to improve the overall toughness of the electrode. The carbon material formed by the carbonization of glucose acts as a binder, tightly bonding the components and further enhancing the integrity and stability of the electrode structure. This synergistic effect ensures that the electrode can maintain the integrity of the structure when it is subjected to the volume changes and mechanical stresses generated during the charge and discharge process, effectively preventing the electrode from breaking and falling off, thereby significantly improving the mechanical strength of the internal structure of the battery. In addition, the synergistic electrode structure shows its unique advantages in improving the safety performance of the battery. During the charge and discharge process, traditional electrode materials are prone to internal short circuits in the battery due to volume expansion and contraction, which in turn causes safety hazards. The synergistic electrode structure of the present invention, through the rigid support of silicon dioxide, the layered stacking of graphite and the bonding effect of glucose carbonized carbon material, jointly constructs a stable and elastic electrode system. This structure can effectively absorb and relieve the stress caused by volume change during the charging and discharging process, reduce the risk of internal short circuit of the battery, and thus significantly improve the safety performance of the battery.

[0021] In the solution of the present invention, another core point is the provided battery assembly process, which helps to improve the stability of the internal electrodes of the battery so as to avoid affecting the performance of the battery.

[0022] The innovative battery assembly process of the present invention plays a vital role in improving the stability of the internal electrodes of the battery. The process is based on advanced material science and electrochemical principles. By precisely controlling various parameters and operating details in the assembly process, the stability of the electrode structure is essentially strengthened. In terms of negative electrode material processing, this process can effectively inhibit the generation of microscopic defects such as cracks and sand holes. Once these defects occur, they will seriously damage the sealing of the battery, causing electrolyte leakage, and then interfere with the complex electrochemical balance inside the battery. At the same time, these defects will also significantly affect the performance of the battery, such as increasing the internal resistance of the battery, reducing the charging and discharging efficiency, and shortening the cycle life of the battery. For the positive electrode material, the process focuses on ensuring the precise construction and effective maintenance of its internal cavity structure. During the battery charging and discharging process, the active material will undergo significant volume changes due to electrochemical reactions. The cavity of the positive electrode material, as a key buffer area, can provide the necessary space for the expansion of the active material, allowing it to stretch freely outward and avoid excessive extrusion of the surrounding structure. This ingenious design effectively alleviates the stress concentration phenomenon inside the battery and greatly reduces the risk of particle breakage caused by excessive stress. Particle breakage can seriously damage the performance of electrode materials, reduce active sites, and thus reduce the overall performance and service life of the battery.

[0023] This technical solution can accurately construct a unique cavity structure using silicon dioxide, manganese dioxide and carbonized glucose carbon chains. From the perspective of electrochemical principles and material mechanics, in the process of battery discharge, the electrode material and the electrolyte will undergo complex electrochemical reactions, which are inevitably accompanied by volume changes. The cavity structure constructed by the present invention is based on a deep understanding and precise response to this phenomenon. The structure can provide an appropriate amount of outward expansion space for the electrode material and the electrolyte after discharge, effectively avoiding the extrusion of the surrounding structure due to insufficient space. Stress concentration is a key issue inside the battery. When the expansion of the electrode material and the electrolyte is limited and the surrounding structure is squeezed, the internal stress will be sharply concentrated. This stress concentration can easily cause the electrode material particles to break, which in turn seriously affects the battery performance. For example, particle crushing will increase the internal resistance of the battery, reduce the battery's charge and discharge efficiency, shorten the battery's cycle life, etc. The cavity structure designed by the present invention greatly reduces the degree of internal stress concentration by allowing the electrode material and the electrolyte to expand moderately outward, thereby significantly reducing the risk of particle crushing caused by stress concentration, and providing a strong guarantee for the stable operation of the battery. Secondly, the unique hollow structure in this scheme is cleverly matched with graphite to form a highly ordered and functional three-dimensional network structure. From the perspective of electron transmission, this three-dimensional network structure is like a dense electron highway network, providing electrons with many efficient and convenient transmission paths. Electrons can move quickly in it, greatly enhancing the efficiency of electron transmission, so that the battery can achieve energy conversion more quickly and stably during the charging and discharging process, and effectively improve the charging and discharging performance of the battery. From the perspective of structural mechanics, the three-dimensional network structure plays a strong mechanical constraint role. It is like a solid frame that tightly wraps and supports the electrode to maintain the overall structural integrity of the electrode. During the charging and discharging process of the battery, the electrode will generate various stresses due to volume changes, and this three-dimensional network structure can effectively disperse and buffer these stresses through mechanical constraints, prevent the electrode structure from deforming and collapsing due to excessive stress, and ensure that the electrode always maintains good physical morphology and electrochemical properties. Finally, the hollow design has unique advantages in optimizing the distribution of electrode pores. By precisely controlling the size, shape and distribution of the hollow structure, it is possible to achieve precise control of the electrode pore size, connectivity and distribution law. This allows the electrolyte to more fully penetrate into various areas inside the electrode, ensuring that ions have a stable and unobstructed transmission channel inside the electrode. Stable ion transmission channels are essential to maintaining the electrochemical performance of the battery. They can ensure that ions migrate quickly and evenly during the charge and discharge process, thereby improving the battery's charge and discharge efficiency, cycle stability, and overall performance.

[0024] The advantages of the present invention are: (1) through the synergistic effect between the various component materials inside the battery, the ion transmission rate, mechanical strength and enhanced safety performance of the battery are improved.

[0025] (2) Through a unique battery assembly process, the cavity distribution of the electrode material unique to the present invention is optimized, the stress concentration inside the battery is reduced, and the electron transmission efficiency is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The figure is a flow chart of the battery production process of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0028] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0029] Example 1: An improved battery production process, the method comprising: (1) using a zinc sheet with a purity of ≥97% to form a cylindrical shell with a diameter of 34 mm and a height of 61.5 mm through a stamping process to obtain a negative electrode material.

[0030] (2) Manganese dioxide, silicon dioxide, graphite powder and glucose were mixed evenly in a mass ratio of 0.1:0.2:4:0.8, reacted at 240 °C for 16 h, then dried at 130 °C for 8 h, and the product was ground into 50 mesh to obtain a positive electrode powder.

[0031] (3) Place a 0.12 mm thick pulp paper into the zinc cylinder, then place the bottom paper into the zinc cylinder, place the positive electrode powder battery cell in the zinc cylinder, perform a negative pressure treatment on the inside of the zinc cylinder with a re-pressure ring, insert a carbon rod, close the zinc cylinder, use sealing glue, add an outer cover and an integrated cover, load it onto a tray and store it, perform a bottom brushing test, put on a trademark, heat shrink the iron bottom, install it into an iron shell, perform the locking procedure, and finally perform heat shrink to prepare an improved battery.

[0032] The battery prepared in the example was subjected to performance testing, and the specific characterization results are as follows.

[0033] Battery internal resistance detection: Connect the current in series with a resistor with a resistance of 3 Ω and a power of 2 W, measure the discharge current of the battery, and calculate the battery internal resistance based on the following formula.

[0034] .

[0035] Where: E is the battery electromotive force, V.

[0036] I'——Measured battery discharge current, A.

[0037] ——Internal resistance of the meter, Ω.

[0038] ——Internal resistance of the series resistor, Ω.

[0039] Battery health status detection: select two batteries prepared in this example, discharge one of them continuously to the end of its life (no further discharge), obtain the old battery that has reached the end of its life after use, measure the AC impedance of the old battery with an AC impedance meter, and obtain the internal resistance of the old battery; discharge the other one continuously to 50% to obtain a test sample battery, measure the AC impedance of the test sample battery with an AC impedance meter, and obtain the internal resistance of the battery; finally, use the AC impedance meter to measure the AC impedance of an unused new battery to obtain the internal resistance of the new battery, and calculate the health status according to the following formula.

[0040] .

[0041] In the formula: SOH——degree of health, %.

[0042] R——Internal resistance of the test sample battery, Ω.

[0043] ——Internal resistance of new battery, Ω.

[0044] ——Internal resistance of old battery, Ω.

[0045] High and low temperature testing: The five batteries prepared in this example were placed in a test box with an ambient temperature of 60°C and kept warm for 168 hours. They were then taken out to measure and calculate the rate of change of the battery internal resistance at this time, and the average value was calculated. The five batteries prepared in this example were placed in a test box with an ambient temperature of -30°C and kept warm for 168 hours. They were then taken out to confirm whether they are operating normally and whether there is any permanent damage. The rate of change of the battery internal resistance at this time was measured and calculated, and the average value was calculated.

[0046] Impact test: Place a 15.8 mm diameter hard rod horizontally on the battery prepared in this example, and drop a 20-pound weight from a height of 610 mm onto the hard rod. Observe and record whether the battery explodes, catches fire, or leaks.

[0047] The test results are shown in Table 1 below.

[0048] Table 1: Performance test table.

[0049]

[0050] Analyzing the characterization results in Table 1 above, in the above test, the health is proportional to the battery health state. The smaller the calculated health, the worse the battery health state. Conversely, the larger the calculated health, the better the battery health state. The high-temperature internal resistance change rate and the low-temperature internal resistance change rate reflect the stability of the battery in high-temperature and low-temperature environments, respectively. Under high-temperature conditions of 60°C, the battery internal resistance change rate is 24.6%, indicating that the battery can still maintain good stability in high-temperature environments, and the internal resistance growth rate is small; under low-temperature conditions of -30°C, the battery internal resistance change rate is 17.4%, and the battery can operate normally without permanent damage, indicating that the battery has strong adaptability in low-temperature environments. The impact test results did not show explosion, fire or leakage, indicating that the prepared battery has good safety performance and can maintain structural integrity when subjected to external impact to avoid safety accidents.

[0051] In addition, according to the UN 38.3 standard, the battery reaction was observed under external short-circuit conditions, and the battery did not catch fire or explode. This shows that the battery has high safety performance under short-circuit conditions. Under overcharge conditions, the battery did not leak, swell or rupture. In the forced discharge test, the battery showed stable discharge characteristics, without abnormal high temperature or voltage drop.

[0052] Example 2: An improved battery production process, the method comprising: (1) using a zinc sheet with a purity of 97% to form a cylindrical shell with a diameter of 34.5 mm and a height of 61.5 mm through a stamping process to obtain a negative electrode material.

[0053] (2) Manganese dioxide, silicon dioxide, graphite powder and glucose were mixed evenly in a mass ratio of 0.1:0.25:4:1, reacted at 250 °C for 14 h, then dried at 140 °C for 7 h, and the product was ground into 100 mesh to obtain a positive electrode powder.

[0054] (3) Place a 0.16 mm thick pulp layer of paper into the zinc cylinder, then place the bottom paper into the zinc cylinder, place the positive electrode powder battery cell in the zinc cylinder, perform a negative pressure treatment on the inside of the zinc cylinder, insert a carbon rod, close the zinc cylinder, use sealing glue, add an outer cover and an integrated cover, load it onto a tray and store it, perform a bottom brushing test, put on a trademark, heat shrink the iron bottom, install it into an iron shell, perform the locking procedure, and finally perform heat shrink to prepare an improved battery.

[0055] The performance of the battery prepared in the example was tested, and the specific characterization results are shown in Table 2 below.

[0056] Table 2: Performance test table.

[0057]

[0058] Analyzing the characterization results in Table 2 above, the battery prepared in this example shows excellent performance in many aspects such as internal resistance, health, high and low temperature stability, and impact safety. The slight decrease in internal resistance indicates that the internal ion conduction of the battery is smoother, which helps to improve the output power and cycle life of the battery. The high value of battery health reflects that it can still maintain a good performance state after undergoing a certain discharge cycle. Compared with Example 1, the battery prepared in this example is optimized and adjusted in terms of the size of the negative electrode material, the preparation conditions and mesh number of the positive electrode powder, and the thickness of the pulp layer paper. Fine-tuning the diameter of the negative electrode material helps to adapt to the design requirements of batteries of different sizes, while changes in the preparation conditions of the positive electrode powder further improve the performance of the positive electrode material. In particular, grinding the product to 100 mesh helps to increase the specific surface area of ​​the positive electrode material and improve the battery reaction activity. The increase in the thickness of the pulp layer paper enhances the sealing and mechanical strength of the battery, further improving the overall performance of the battery.

[0059] In addition, according to the UN 38.3 standard, the battery reaction was observed under external short-circuit conditions, and the battery did not catch fire or explode. This shows that the battery has high safety performance under short-circuit conditions. Under overcharge conditions, the battery did not leak, swell or rupture. In the forced discharge test, the battery showed stable discharge characteristics, without abnormal high temperature or voltage drop.

[0060] Example 3: An improved battery production process, the method comprising: (1) using a zinc sheet with a purity of 97% to form a cylindrical shell with a diameter of 35 mm and a height of 62 mm through a stamping process to obtain a negative electrode material.

[0061] (2) Manganese dioxide, silicon dioxide, graphite powder and glucose were mixed evenly in a mass ratio of 0.1:0.3:4:1.2, reacted at 260 °C for 12 h, then dried at 150 °C for 6 h, and the product was ground into 150 mesh to obtain a positive electrode powder.

[0062] (3) Place a 0.2 mm thick pulp paper into the zinc cylinder, then place the bottom paper into the zinc cylinder, place the positive electrode powder battery cell in the zinc cylinder, perform a negative pressure treatment on the inside of the zinc cylinder, insert the carbon rod, close the zinc cylinder, use sealing glue, add an outer cover and an integrated cover, load it onto a tray and store it, perform a bottom brushing test, put on a trademark, heat shrink the iron bottom, install it into the iron shell, perform the locking procedure, and finally perform heat shrink to prepare an improved battery.

[0063] The battery prepared in the example was subjected to performance testing, and the specific characterization results are shown in Table 3 below.

[0064] Table 3: Performance test table.

[0065]

[0066] Analyzing the characterization results in Table 3 above, the battery prepared in this example shows excellent performance in many aspects such as internal resistance, health, high and low temperature stability, and impact safety. Comprehensive analysis of the characterization results of Examples 1 to 3 shows that the internal resistance shows a slight downward trend. Reducing the internal resistance means that the ion conduction process inside the battery becomes smoother. As a medium for charge transfer inside the battery, the conduction efficiency of ions is directly related to battery performance. When the ion movement efficiency is improved, the output power of the battery is significantly enhanced, so that it can power the device more quickly and stably in practical applications. At the same time, the optimization of internal resistance has a positive effect on the cycle life of the battery, reducing energy loss during charging and discharging, thereby extending the normal use cycle of the battery. Secondly, the health of the battery is maintained at a high level. This feature fully proves that even if the battery is overused, its performance can still be maintained in an excellent state. Even during long-term use, the various performance indicators of the battery have not declined significantly, thus demonstrating its excellent durability and reliability.

[0067] In addition, according to the UN 38.3 standard, the battery reaction was observed under external short-circuit conditions, and the battery did not catch fire or explode. This shows that the battery has high safety performance under short-circuit conditions. Under overcharge conditions, the battery did not leak, swell or rupture. In the forced discharge test, the battery showed stable discharge characteristics, without abnormal high temperature or voltage drop.

[0068] Comparative Example 1: An improved battery production process, the specific preparation method of which is the same as that of Example 2. The comparative example only changes the positive electrode powder component in the present invention and uses an equal amount of graphene powder instead. The specific characterization results and operation process are as follows.

[0069] (1) A zinc sheet with a purity of 97% was made into a cylindrical shell with a diameter of 34.5 mm and a height of 61.5 mm by a stamping process to obtain a negative electrode material.

[0070] (2) The graphene powder was dried at 140 °C for 7 h and the product was ground into 100 mesh to obtain positive electrode powder.

[0071] (3) Place a 0.16 mm thick pulp layer of paper into the zinc cylinder, then place the bottom paper into the zinc cylinder, place the positive electrode powder battery cell in the zinc cylinder, perform a negative pressure treatment on the inside of the zinc cylinder, insert a carbon rod, close the zinc cylinder, use sealing glue, add an outer cover and an integrated cover, load it onto a tray and store it, perform a bottom brushing test, put on a trademark, heat shrink the iron bottom, install it into an iron shell, perform the locking procedure, and finally perform heat shrink to prepare an improved battery.

[0072] The battery prepared in the example was subjected to performance testing, and the specific characterization results are shown in Table 4 below.

[0073] Table 4: Performance test table.

[0074]

[0075] Analyzing the characterization data in Table 4 above, compared with Example 2, the battery in Comparative Example 1 shows a significant deterioration trend in multiple performance indicators. Specifically, the internal resistance increases significantly. This phenomenon is deeply analyzed from the perspective of electrochemical principles, and the ion conduction process inside the battery encounters serious obstacles. As the core link of the electrochemical reaction of the battery, the obstruction of ion conduction will inevitably have a negative impact on the output power of the battery, resulting in the battery being unable to efficiently convert chemical energy into electrical energy output. At the same time, the continuous poor ion conduction will also accelerate the irreversible damage of the electrode materials inside the battery, thereby shortening the cycle life of the battery and limiting the sustainable use time of the battery in practical applications. The battery health is significantly reduced, and further analysis shows that this performance degradation is closely related to the adjustment of the positive electrode powder components. Although graphene powder has excellent intrinsic conductivity, its excellent characteristics have not been effectively stimulated and utilized under the current specific production process system. On the contrary, the introduction of graphene powder may change the microstructure and interface properties of the positive electrode material, destroying the ordered structure that is originally conducive to ion conduction and charge transfer, thereby causing a decline in battery performance. In the high and low temperature stability test, the battery of Comparative Example 1 exposed poor environmental adaptability. Specific data show that its high-temperature internal resistance change rate and low-temperature internal resistance change rate are significantly higher than those in Example 2. From the perspective of thermophysics and electrochemical coupling, this phenomenon shows that the physical and chemical processes inside the battery change in a way that is not conducive to stable performance under high and low temperature environments. This change is highly attributed to the change in the preparation process of the positive electrode powder and the intervention of graphene powder, which work together to affect the thermal stability of the battery material and the conduction kinetics of ions under different temperature fields, making it difficult for the battery to maintain stable electrochemical performance under extreme temperature conditions. Nevertheless, in the impact test, the battery of Comparative Example 1 exhibited good safety performance. Even when subjected to high-intensity external impacts, the battery did not experience serious safety accidents such as explosion, fire or leakage. This phenomenon shows that the production process has certain scientific rationality and advancement in battery structure design. Through clever structural layout and material selection, it is possible to buffer and disperse external impact forces to a certain extent, ensuring that key components such as electrode materials and electrolytes inside the battery remain relatively stable when subjected to impact, thereby effectively ensuring the safety of the battery under extreme mechanical stress conditions.

[0076] Comparative Example 2: An improved battery production process, whose specific preparation method is the same as Example 2. The comparative example only changes the battery assembly steps in the present invention and uses common technical solutions to assemble the battery. The specific characterization results are shown in Table 5 below.

[0077] Table 5: Performance test table.

[0078]

[0079] Analyzing the characterization data in Table 5 above, compared with Example 2, the battery in Comparative Example 2 shows a significant downward trend in various performance dimensions. From the perspective of the change in internal resistance parameters, its internal resistance shows a significant increasing trend. According to the basic principles of electrochemistry, the increase in internal resistance means that the resistance of the ion conduction path inside the battery increases, and the migration process of ions between the electrode and the electrolyte is significantly hindered. This obstruction directly affects the kinetic process of the electrochemical reaction inside the battery, causing the battery to face greater energy loss when outputting electrical energy, which inevitably leads to a decrease in the battery output power. At the same time, due to the obstruction of ion conduction, the stability of the electrode structure is destroyed, which undoubtedly accelerates the decay of the battery capacity and ultimately causes the cycle life of the battery to be greatly shortened. The battery health is significantly reduced, which also reflects the deterioration of the battery performance in Comparative Example 2. In-depth analysis shows that this performance degradation is very likely related to the modification of the battery assembly steps. The battery assembly process provided by the present invention helps to improve the stability of the internal electrodes of the battery, effectively prevents defects such as cracks and sand holes in the negative electrode material area, thereby avoiding affecting the sealing and performance of the battery. At the same time, ensure the existence and reasonable distribution of the positive electrode material cavity, so that the active material can expand outward without squeezing the surrounding structure, thereby reducing the risk of particle breakage caused by internal stress concentration. In addition, the three-dimensional network structure formed by the hollow structure and graphite not only improves the efficiency of electron transmission, but also maintains the integrity of the electrode as a whole through mechanical constraints. In the high and low temperature stability test, the battery of comparative example 2 exposed poor environmental adaptability, and its high temperature internal resistance change rate and low temperature internal resistance change rate were both at a high level. According to the principle of thermochemical and electrochemical coupling, under high temperature environment, the chemical reaction rate inside the battery is accelerated, which may cause problems such as decomposition of the electrolyte and decreased thermal stability of the electrode material, resulting in a sharp increase in internal resistance; while in a low temperature environment, the viscosity of the electrolyte increases and the ion diffusion coefficient decreases, further increasing the difficulty of ion conduction, which also causes a significant increase in internal resistance. This series of changes fully demonstrates that the internal physical and chemical processes of the battery are difficult to maintain stability under extreme temperature conditions, resulting in poor battery performance stability. In particular, the battery of Example 2 leaked during the impact test, which indicates that there are defects in the internal structure of the battery, resulting in the battery being unable to maintain structural integrity when subjected to external impact. The present invention introduces a backing paper with a micro-textured structure on the contact surface between the battery casing and the internal components through the cooperation of external processing and electrode materials. The change in the microstructure can effectively increase the mechanical engagement area between the two contact surfaces, which is similar to a "lock" structure at the micro level, thereby enhancing the connection strength between the two at a macro level and improving the battery's impact resistance.

[0080] Comparative Example 3: A commercially available dry battery was subjected to the same performance test as in Example 1. The specific characterization results are shown in Table 6 below.

[0081] Table 6: Performance test table.

[0082]

[0083] Analyzing the characterization results in Table 6 above, compared with Example 2, the performance of the commercially available battery in Comparative Example 3 is significantly inferior. Among them, the increase in the internal resistance of the battery will cause the voltage output by the battery to drop, and the internal resistance will produce a voltage drop, making the actual output voltage lower than the theoretical value. This voltage drop will affect the normal operation of the battery-powered equipment and shorten the effective use time of the battery. The health index is low, indicating that the performance of the battery declines rapidly after long-term use and has poor durability. In the high and low temperature stability test, the high temperature internal resistance change rate and the low temperature internal resistance change rate of the commercially available dry battery are both at a high level, showing that its adaptability to environmental changes is weak. In particular, in the impact test, the commercially available battery leaked, which further verified the deficiencies in its structural design and the hidden dangers in safety.

Claims

1. An improved battery production process, characterized in that: The process includes: 1) using high-purity zinc as a raw material to manufacture a cylindrical shell, which is a negative electrode; 2) using manganese dioxide, silicon dioxide, graphite powder and glucose as raw materials to prepare a positive electrode material, and grinding it into a positive electrode powder; 3) filling, assembling and sealing the cylindrical shell and the positive electrode powder to prepare an improved battery.

2. An improved battery production process according to claim 1, characterized in that: The high-purity zinc in step 1) is metallic zinc with a purity of ≥97.0 wt%; the manufacturing of the cylindrical shell in step 1) is achieved through a stamping process.

3. The improved battery production process according to claim 1, characterized in that: In step 2), the mass ratio of manganese dioxide, silicon dioxide, graphite powder and glucose is 0.1: (0.2-0.3): 4: (0.8-1.2).

4. An improved battery production process according to claim 1 or 3, characterized in that: Step 2) The process of preparing the positive electrode material is: manganese dioxide, silicon dioxide, graphite powder and glucose are uniformly mixed in proportion, reacted at a temperature of 240 to 260°C for 12 to 16 hours, and then dried at a temperature of 130 to 150°C for 6 to 8 hours.

5. The improved battery production process according to claim 1, characterized in that: Step 2) The mesh size of the positive electrode powder is 50-150 meshes.

6. The improved battery production process according to claim 1, characterized in that: Step 3) The filling, assembling and sealing process is as follows: put the pulp layer paper into the zinc cylinder, then put the bottom paper into the zinc cylinder, place the positive electrode powder battery cell in the zinc cylinder, perform negative pressure treatment on the inside of the zinc cylinder with a re-pressure ring, insert the carbon rod, close the zinc cylinder, use sealing glue, add an outer cover and an integrated cover, and then put it on a tray for storage.

7. An improved battery production process according to claim 6, characterized in that: The products loaded and stored in the tray are subjected to bottom brushing and electricity testing, and the iron bottom is heat-shrunk, loaded into the iron shell, and the locking procedure is performed, and finally the heat-shrunk is performed.

Citation Information

Patent Citations

  • Method for manufacturing plastic housing battery

    CN101533913A

  • Valve-controlled sealed lead-acid accumulator for electric vehicle

    CN102110797A

  • Preparation method of doped Li4Ti5O12 anode material

    CN104810515A

  • Mercury-free high-power zinc-manganese battery and battery cell powder thereof, zinc barrel and mercury-free coated paper

    CN109494382A

  • New manganese dioxide electrodes, process for producing the same and their use

    CN1246203A